A representação da deficiência na literatura infanto-juvenil nos tempos de inclusão - Noronha, Lucelia Fagundes Fernandes (2007)
The purpose of this study is to analyze how impairment was showed in the infant juvenile literature in the books published to Brazilian authors for the first time in the years from 1996 to 2006. Coming from the initial hypothesis that in this historical moment, in which social and school inclusion of the impaired person as an ideal of citizenship are thought, infant juvenile literature, being a cultural product present in kids lives may contribute to diminish as well as to disseminate prejudice in relation to handicap. Before getting to the result a way aiming at highlighting the definitions about impairment, about prejudice, about stereotypes and stigma was taken, as well as about inclusion. In this theoretical way, still, some fundaments about culture, society and education in the social representing theory were searched. The methodology adopted involved a quantitative and qualitative treatment of the data collected and for the performing of an analysis of the same, complex and interactive parameters were used in relation to the categories proposed, involving: the narrator, the plot, the type of discourse, the type of impairment or difference, the characters in dramatic context, the characteristics and actions, the nomination, the attribution fields of the phenomena in the etiology of impairment and in the closure of the story. The data were presented by a summary of the story, respective card of material exploration, of the quantitative result and qualitative analysis. After performing the content analysis of the stories, three tendencies were revealed: stories free from prejudice, denouncing stories, but simultaneously, perpetuators of prejudice,stereotypes and/or stigmas in relation to impairment. With this research it was possible to extract a little from this unending vein, of this rich material and this enchantment source of juvenile books, which might be simultaneously, source of pleasure, reflection and of critics.